The role of macroprudential policy for financial stability in East Asia's emerging economies - Yung Chul Park (Asian Development Bank Institute (ADBI), 2011)
This paper analyzes the role and scope of macroprudential policy in preventing financial instability in the context of East Asian economies. It analyzes the behavior of the housing market in a dynamic setting to identify some of the factors responsible for the volatility of housing markets and their susceptibility to boom-bust cycles, which it identifies as a key source of financial imbalances in these economies. It then discusses the causal nexus between price and financial stability and the roles and complementary nature of macroprudential and monetary policies in addressing aggregate risk in the financial system. The paper identifies currency and maturity mismatches, which contributed to the 1997 - 1998 Asian financial crisis, as ongoing concerns in these economies although the high levels of reserves in the region now act as a buffer.
Keywords: E52; E58; G01; G15; G28; 330; Finanzmarktkrise; Immobilienpreis; Geldpolitik; Kapitalmarktliberalisierung; Schwellenländer; Ostasien